A common 40 amino acid motif in eukaryotic RNases H1 and caulimovirus ORF VI proteins binds to duplex RNAs. - Cerritelli, S M (1998)
Eukaryotic RNases H from Saccharomyces cerevisiae , Schizosaccharomyces pombe and Crithidia fasciculata , unlike the related Escherichia coli RNase HI, contain a non-RNase H domain with a common motif. Previously we showed that S.cerevisiae RNase H1 binds to duplex RNAs (either RNA-DNA hybrids or double-stranded RNA) through a region related to the double-stranded RNA binding motif. A very similar amino acid sequence is present in caulimovirus ORF VI proteins. The hallmark of the RNase H/caulimovirus nucleic acid binding motif is a stretch of 40 amino acids with 11 highly conserved residues, seven of which are aromatic. Point mutations, insertions and deletions indicated that integrity of the motif is important for binding. However, additional amino acids are required because a minimal peptide containing the motif was disordered in solution and failed to bind to duplex RNAs, whereas a longer protein bound well. Schizosaccharomyces pombe RNase H1 also bound to duplex RNAs, as did proteins in which the S.cerevisiae RNase H1 binding motif was replaced by either the C.fasciculata or by the cauliflower mosaic virus ORF VI sequence. The similarity between the RNase H and the caulimovirus domain suggest a common interaction with duplex RNAs of these two different groups of proteins.